ETIKA, PROFESI DOSEN DAN PERGURUAN TINGGI: SEBUAH KAJIAN KONSEPTUAL - Arum Ardianingsih; Siti Yunitarini (Fakultas Ekonomi Universitas Pekalongan, 2015)
University is place to produced of professional human resource for have qualification in science area and ethical behaviour. Universities have a duty to establish